2014
DOI: 10.9755/ejfa.v26i8.17178
|View full text |Cite
|
Sign up to set email alerts
|

Biofertilizer effects in combination with different drying system and storage period on growth and production of tomato plant under field conditions

Abstract: Low soil fertility is caused by continue crop and using chemical fertilizer. The biofertilizer contains microorganism able to increase soil fertility. The purpose of this research was to investigate the effect of biofertilizer dried by different methods and exposed to different period of storage on nutrient, growth and productivity of tomato plant grown under the field conditions. The experiment was carried out at the field experimental Station, Research Center of Vegetable Crop, Lembang, Bandung West Java, In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 11 publications
0
11
0
2
Order By: Relevance
“…For this reason, the existence of plant species having ability to absorb high metal concentration, known as metals hyperaccumulator, is very important. In addition, the use of microbes to induce plant growth either from bacteria (Mahfouz and Sharaf-Eldin 2007;Altuhaish et al 2014) or fungi (Augé 2001;Smith et al 2010) also increased dramatically, which may relate to the important mechanism in phytoremediation process (Rozpadek et al 2014). Many experiments also suggested that mycorrhizas fungi have important role in phytoremediation process by improving plant growth and inducing metal accumulation (Weissenhorn et al 1995;Javaid 2011;Khan et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the existence of plant species having ability to absorb high metal concentration, known as metals hyperaccumulator, is very important. In addition, the use of microbes to induce plant growth either from bacteria (Mahfouz and Sharaf-Eldin 2007;Altuhaish et al 2014) or fungi (Augé 2001;Smith et al 2010) also increased dramatically, which may relate to the important mechanism in phytoremediation process (Rozpadek et al 2014). Many experiments also suggested that mycorrhizas fungi have important role in phytoremediation process by improving plant growth and inducing metal accumulation (Weissenhorn et al 1995;Javaid 2011;Khan et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It has deep roots systems and produces high amount of organic matter, which is necessary to accelerate the reclamation process (Sheoran et al 2010). Organic matters can improve soil fertility through microbe activities (Mimmo et al 2004) by decomposing mineral and organic matters and also promoting plant growth (Beneduzi et al 2012;Altuhaish et al 2014;Grobelak et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Tsavkelova et al (2012) reported that IAA and other phytohormones production depend on the stage of colonization, host plant and fungus infection strategy. Altuhaish et al (2014), reported the existence of plant hormones produced by rhizobacteria that improves growth and development of root cells, to become more extensive absorption, which in turn to increase plant nutrient uptake. Future studies are required to test the ability of microorganisms evaluated in this study in order to improve the growth promotion of guanandi seedlings.…”
Section: Resultsmentioning
confidence: 99%